2003
DOI: 10.1046/j.1464-5491.2003.00782.x
|View full text |Cite
|
Sign up to set email alerts
|

High incidence of Type 2 diabetes mellitus in South African Indians: a 10‐year follow‐up study

Abstract: This long-term study has shown that in South African Indians there is a high incidence of Type 2 diabetes, and in this population significant predictors include higher baseline blood glucose, BMI and obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
42
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 39 publications
(148 reference statements)
3
42
0
1
Order By: Relevance
“…16 The sharp increase in the prevalence of type 2 diabetes between these studies may be due to the geographical location of these populations, significant differences in obesity, their economic transition, and the different criteria used for diagnosing diabetes. The limited studies in South Africa have shown a positive rural-to-urban gradient in terms of the prevalence of type 2 diabetes, [2][3][4]12 and the sample for this study was taken from an urban coloured population located approximately 50 km from the previous study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 The sharp increase in the prevalence of type 2 diabetes between these studies may be due to the geographical location of these populations, significant differences in obesity, their economic transition, and the different criteria used for diagnosing diabetes. The limited studies in South Africa have shown a positive rural-to-urban gradient in terms of the prevalence of type 2 diabetes, [2][3][4]12 and the sample for this study was taken from an urban coloured population located approximately 50 km from the previous study.…”
Section: Discussionmentioning
confidence: 99%
“…1 This population has the second-highest prevalence of diabetes in South Africa, after that of the Indian population. [2][3][4] However, this finding was based on a study almost 20 years ago in a peri-urban coloured population of the Western Cape. 2 Since then, South Africa has undergone significant political changes that have been accompanied by rapid urbanisation and economic changes, particularly among the coloured and other non-white population groups.…”
mentioning
confidence: 99%
“…However, a number of epidemiological studies have been conducted in selected communities in the 1980s and 1990s. [5][6][7][8][9][10] These revealed a clear rural-urban gradient with higher prevalence in urban settings, in addition to a gradient across different population groups. Studies reported the highest prevalence in the Indian population, followed by the coloured and then the black population.…”
mentioning
confidence: 99%
“…In a 10-year follow-up study of South African Indian subjects, at baseline, the crude prevalences of DM and IGT were found to be 9.8% and 5.8% respectively. 9 Screening a group of Zulu subjects for DM revealed a prevalence of 5.3% for DM and 7.7% for IGT when adjusted for age and sex. 10 In the surveys conducted in populations in sub-Saharan Africa there was considerable variation in the categorisation of individuals using the ADA and old WHO criteria.…”
mentioning
confidence: 99%